Monitoring Departure to Schools in Basic School Students Using Arduino Based on Android - Eko Saputro; Anggraini Kusumaningrum; Mardiana Irawaty (SENATIK STT Adisutjipto, 2018)
Student departure monitoring is an Android-based app used to monitor student departure to school. This system runs on parent smartphones so parents can see the existence of students and the app will give a message if the student out of the route path that has been set. Arduino used is arduino uno nano type. Arduino programmed using C language, to monitor the existence of students also required some components such as GSM Module and GPS Module. In testing the user application can monitor the existence of the students through the mobile phone that has been installed the application, before monitoring the departure of parents students are required to enter data coordinates home, coordinate data route and data coordinates of schools entered manually. To get the coordinate data the parent can take it through google Maps. To avoid failure in the use of remote control applications should use Android smartphone version 4.1 Jelly bean to version 6.0 Marshmallow. In the experiments this application can run smoothly with the Android version 4.1 to Android version 6.0 and the results of the questionnaire given to the 30 respondents with 9 questions 75.77% results obtained using Likert-scale calculations, which results obtained a good assessment interval.